Sleep disruption due to nocturnal heartburn: a review of the evidence and clinical implications - David A. Johnson; Amisha M. Parikh-Das; Evren Atillasoy; Hayk Davtyan; Leslie Shur; Andrea S. Blevins-Primeau; Nathaniel F. Watson (Open Exploration Publishing Inc., 2023)
Nocturnal heartburn (NHB) is a symptom that affects up to 25% of the general population and has been shown to cause sleep disruption that adversely affects quality of life and psychomotor performance. Few studies have evaluated the association between occasional NHB and sleep disturbances; therefore, this connection may be underappreciated and left untreated by the primary care provider and patient, with potentially significant negative clinical consequences and effects on quality of life. This review sought to describe what is currently known about the interplay between occasional NHB and sleep disruption, and identify whether acid suppression therapy can improve symptoms of occasional NHB and associated sleep disruptions. The pathophysiology of heartburn-induced sleep disruption appears to follow a bidirectional cycle due to the normal physiologic changes that occur in the upper gastrointestinal tract during sleep and due to the potential for heartburn symptoms to cause sleep arousal. The majority of the identified studies suggested that pharmacologic interventions for acid reduction, including proton pump inhibitors or histamine type-2 receptor antagonists (H2RAs), improved objective and/or subjective sleep outcomes among individuals with gastroesophageal reflux disease (GERD) and NHB. Several studies specific to famotidine demonstrated that treatment with 10 mg or 20 mg reduced nighttime awakenings due to NHB. In conclusion, NHB symptoms can cause sleep dysfunction that can have a profound adverse downstream effect on quality of life, next-day functioning, and health-related outcomes. The current approach to managing occasional NHB is similar to that associated with GERD, highlighting the need for studies specific to the occasional heartburn population. Health care providers should investigate NHB as one of the potential causes of sleep complaints, and patients with heartburn should be questioned about sleep quality, recalled arousals, next-day vitality, early fatigue, and next-day functioning.